A review of organic small molecule-based hole-transporting materials for meso-structured organic–inorganic perovskite solar cells. Issue 41 (23rd September 2016) - Teh, Chin Hoong; Daik, Rusli; Lim, Eng Liang; Yap, Chi Chin; Ibrahim, Mohd Adib; Ludin, Norasikin Ahmad; Sopian, Kamaruzzaman; Mat Teridi, Mohd Asri
Abstract : HTMs with a planar core structure, extended-π system and electron-rich groups exhibited better intrinsic conductivity, which enhanced the photovoltaic performance. Abstract : This review summarizes the current designs and development of new types of organic small molecules as a hole-transporting material (HTM) in a meso-structured perovskite solar cell (PSC). The roles of each layer in the meso-structured perovskite device architecture are elaborated and the employment of new types of organic HTMs in the device is compared with the commercially available HTM spiro-OMeTAD in terms of the properties, device performance and stability. The studies found that nearly half of the new synthesized and pristine HTMs have comparable or better photovoltaic properties than those of doped spiro-OMeTAD. These HTMs have the characteristics of a fused planar core structure with extended π-conjugated lengths and electron-donating functional groups, which are believed to contribute to their high intrinsic conductivity and help make them an alternative to spiro-OMeTAD as a better HTM in meso-structured PSCs. Some of the devices based on the new synthesized HTMs even have longer device lifetimes than their spiro-OMeTAD-based PSC counterparts. Moreover, studies found that the cost per gram ( C g ) and cost-per-peak Watt ( C w ) of synthesized HTMs can be reduced via minimizing the number of synthesis steps and by optimization of the starting materials in order to yield low-cost HTMs for meso-structured PSC applications.